2016
DOI: 10.5194/ascmo-2-1-2016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hidden and observed regime-switching autoregressive models for (<i>u</i>, <i>v</i>)-components of wind fields in the northeastern Atlantic

Abstract: Several multi-site stochastic generators of zonal and meridional components of wind are proposed in this paper. A regime-switching framework is introduced to account for the alternation of intensity and variability that is observed in wind conditions due to the existence of different weather types. This modeling blocks time series into periods in which the series is described by a single model. The regime-switching is modeled by a discrete variable that can be introduced as a latent (or hidden) variable or as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Environmental data often exhibit departures from Gaussianity, such as skewness and heavy tails. Traditionally, to continue exploiting the appealing properties of the normal distribution and the well‐developed theory of Gaussian processes, a transformation is usually applied to the data; for example, a square root transformation (Gneiting, ), a power transformation (Ailliot et al ; Bessac et al ) or a Gaussian copula (Hering et al ). Only recently have there been studies that exploit the flexibility of skew‐elliptical distributions, of which the skew‐ t (Azzalini and Capitanio, ) and the skew‐normal (Azzalini, ) distributions are special cases that directly address the skewness and excess kurtosis that are commonly found in wind data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental data often exhibit departures from Gaussianity, such as skewness and heavy tails. Traditionally, to continue exploiting the appealing properties of the normal distribution and the well‐developed theory of Gaussian processes, a transformation is usually applied to the data; for example, a square root transformation (Gneiting, ), a power transformation (Ailliot et al ; Bessac et al ) or a Gaussian copula (Hering et al ). Only recently have there been studies that exploit the flexibility of skew‐elliptical distributions, of which the skew‐ t (Azzalini and Capitanio, ) and the skew‐normal (Azzalini, ) distributions are special cases that directly address the skewness and excess kurtosis that are commonly found in wind data.…”
Section: Introductionmentioning
confidence: 99%
“…2002), a power transformation (Ailliot et al, 2015b;Bessac et al, 2016) or a Gaussian copula . Only recently have there been studies that exploit the flexibility of skew-elliptical distributions, of which the skew-t (Azzalini and Capitanio, 2003) and the skew-normal (Azzalini, 2005) distributions are special cases that directly address the skewness and excess kurtosis that are commonly found in wind data.…”
Section: Introductionmentioning
confidence: 99%
“…It leads to a VAR model for dry days and an other VAR model for wet days (Richardson, 1981). The MSVAR model is more general since the regimes are not observed (see (Bessac et al, 2016) for a comparison of models with observed and latent regimes for wind data). (1) Rennes (2) Le Mans (3) Paris (4) Beauvais (5) Strasbourg (6) Vichy (7) Biarritz (8) Toulouse (9) Carcassone (10) Nimes (11) Mont−Aigoual (12) Figure 1: Considered stations.…”
Section: Daily Temperature Time Seriesmentioning
confidence: 99%
“…This model is a mixture of three autoregressive models which accommodate "rising", "falling" and "normal" states in the runoff process. (Bessac et al, 2016) and proposed Markov Switching VAR models to exhibit wind regimes from multivariate meteorological time series. These models are common for econometric time series too (Hamilton, 1989) (Krolzig, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation